Unjuk Kerja Waduk Jatigede - Cholifatul Afifah, Risdiana; Samto Atmodjo, Pranoto; Sangkawati, Sri (Department of Civil Engineering, Diponegoro University, 2015)
Jatigede Reservoir located in Sumedang, West Java. As the second largest reservoir in Indonesia, the main purpose of the reservoir construction is to irrigate the 90.000 Ha of irrigation area, the source of 3,5 m3/s of raw and drinking water, as well as the source of water for hydropower plan Jatigede requiring water supply as much as 61,84 m3/s. One of the efforts that can be taken to optimize reservoir of water resources, particularly for irrigation water needs, is to do a simulation model of the Jatigede Reservoir operation. This study is discusses the analysis of the performance of the operating pattern Jatigede were analyzed based on the stochastic model of Cimanuk river flow and rain data of Cimanuk Water District. Data needs to be tested first to qualify for a normal statistical distribution using AProb software version 4.1. Stochastic models were analyzed with software SAMS 2007 from Colorado State University. Surgery simulation analysis to determine the performance of the reservoir using software Ribasim. To test the performance of reservoir used the criteria of reliability, resilience, and vulnerability. From the analysis of performance can be concluded that the reliability of the reservoir in an effort to meet the needs of raw water, irrigation, and hydropower at existing condition is of 98.3%, the resilience of the reservoir by 50%, and the vulnerability of dams throughout the simulation period amounted to 6824.70 m3/s , While in the next 50 years the condition of the dam by 92.7% reliability, resilience reservoir by 34%, and the vulnerability of dams throughout the simulation period amounted 20.540,51m3/s. It can be concluded that the performance of Jatigede reservoir decreased after the analysis of reservoir operation plan for the next 50 years.